Inflation Targeting and Country Risk : An Empirical Investigation - Fouejieu, Armand (IMF Working Papers; Working Paper ;, 2013)
The sovereign debt crisis in Europe has highlighted the role of country risk premia as a link between countries' fiscal and external balances, financial conditions and monetary policy. The purpose of this paper is to estimate how adoption of inflation targeting (IT) affects spreads. It is hypothesized that country risk premia for IT countries (especially among emerging market economies) may be lower than for other countries owing to greater policy predictability and more stable long-term inflation. The findings suggest that IT reduces the risk premium, both through adoption of the IT regime, and through the observed track record in stabilizing inflation.